Words in Place: Mapping Australian Literature - Toby DAVIDSON; John POTTS (E-REA)
This article considers literary mapping as an instance of the contemporary construction of space through digital networked technology. Digital cartography – mapping with the means of digital technology, internet and GPS technologies – represents space as a virtual layering of information. The digital cartography project Words in Space is discussed as a case study of digital literary mapping. Analysis of the data contained in this literary map reveals significant aspects of literary commemoration in Australia.